Position and relations of ovary in developing human fetuses - Ambath D Momin; Naranbabu Singh (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of the study is to relook into the gross development of human ovary and its relation to other pelvic organs. Materials and methods: The materials studied consisted of 52 normal human female fetuses of different gestational ages starting from 14th week to 40 weeks, collected from Dept. of Obstetrics and Gynecology, RIMS, Imphal with permission from the local ethical committee. Results: The ovaries are almond shaped and are located in false pelvis till term. The orientations of the ovaries were different at different age groups. Till 16 week the ovary was found to be placed vertically, at 18 weeks obliquely in 66.66% and vertically in 33.33% instances. Thereafter ovaries were placed obliquely in the false pelvis till 29th week. At 30th week they were found to be almost horizontal till 38th week of gestation and at 40th week they regained oblique orientation. Weight and all the dimensions of the ovary were found to increase with increasing gestational weeks. The weight and dimension of right ovary was slightly more than that of left ovary. During early weeks ovarian size is greater than that of uterus but as the age advances, size of uterus becomes bigger than ovary. Conclusion: Ovaries lie vertically in early weeks of gestation and become oblique in mid trimester. The ovary becomes temporarily horizontal at the end of third trimester only to become oblique at term. The detailed knowledge of developmental anatomy will help the clinician to deal with the diseases related to ovary.